2016
DOI: 10.1039/c5ee02950c
|View full text |Cite
|
Sign up to set email alerts
|

Calcium looping with inherent energy storage for decarbonisation of coal-fired power plant

Abstract: Carbon capture and storage (CCS) with energy storage (ES) systems increase flexibility and profitability of fossil-fuel-fired power systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 59 publications
(81 reference statements)
3
64
0
Order By: Relevance
“…Such a system can achieve high energy density and specific energy of 315.9 kWelh/m 3 and 885.2 kJ/kg, respectively ( Dm=108-180 kJ/kg [21,22]), and Li-ion batteries (DV=200-500 kWelh/m 3 ; Dm=270-720 kJ/kg [21,22]). This proves that such a system can be expected to improve flexibility and profitability of the oxy-combustion CFPP, and other CO2 capture systems such as calcium looping [18] or chemical looping combustion, by providing means that would allow utilising the daily variation in electricity price. An analysis of the thermodynamic performance for the selected cases ( Table 3) has revealed that modification of the reference air-combustion CFPP to the oxycombustion CFPP (Case 1) results in an efficiency penalty of 11.0-11.7%HHV points, depending on the operating load of the system.…”
Section: Thermodynamic Performance Evaluationmentioning
confidence: 94%
See 4 more Smart Citations
“…Such a system can achieve high energy density and specific energy of 315.9 kWelh/m 3 and 885.2 kJ/kg, respectively ( Dm=108-180 kJ/kg [21,22]), and Li-ion batteries (DV=200-500 kWelh/m 3 ; Dm=270-720 kJ/kg [21,22]). This proves that such a system can be expected to improve flexibility and profitability of the oxy-combustion CFPP, and other CO2 capture systems such as calcium looping [18] or chemical looping combustion, by providing means that would allow utilising the daily variation in electricity price. An analysis of the thermodynamic performance for the selected cases ( Table 3) has revealed that modification of the reference air-combustion CFPP to the oxycombustion CFPP (Case 1) results in an efficiency penalty of 11.0-11.7%HHV points, depending on the operating load of the system.…”
Section: Thermodynamic Performance Evaluationmentioning
confidence: 94%
“…Considering the variability in daily energy prices and grid demand, application of cryogenic O2 storage was found to be a feasible option to enable flexible operation of the nuclear power plant [40] and increase profitability of the air-combustion CFPP retrofitted with the calcium looping process by up to 2.3%. The latter system was shown to produce higher profits in the current economic climate than the air-combustion CFPP without CO2 capture, regardless of the efficiency penalty of 8.6%HHV points [18]. The technoeconomic feasibility of implementing peak and off-peak operation of the ASU in the oxy-combustion CFPP has been proven by Hu et al [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations